2018
DOI: 10.1038/s41598-018-26083-3
|View full text |Cite
|
Sign up to set email alerts
|

Early Salmonella Typhimurium infection in pigs disrupts Microbiome composition and functionality principally at the ileum mucosa

Abstract: Salmonella is a major foodborne pathogen which successfully infects animal species for human consumption such as swine. The pathogen has a battery of virulence factors which it uses to colonise and persist within the host. The host microbiota may play a role in resistance to, and may also be indirectly responsible from some of the consequences of, Salmonella infection. To investigate this, we used 16S rRNA metagenomic sequencing to determine the changes in the gut microbiota of pigs in response to infection by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
70
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 52 publications
10
70
1
Order By: Relevance
“…However, these genera were hardly detected in our samples, while the most abundant genus was undoubtedly Lactobacillus (>97%). This is in agreement with the results of Argüello et al (2018) [63] who found Lactobacillus levels of about 60% in 5 week-old piglets. Lactobacilli might have been stimulated by the lactose present in the diet (4%), as these bacteria are able to use the simple milk sugar for their energy production [66].…”
Section: Effects Of Thymol and Tαg Supplementation On Gut Microbiotasupporting
confidence: 94%
See 2 more Smart Citations
“…However, these genera were hardly detected in our samples, while the most abundant genus was undoubtedly Lactobacillus (>97%). This is in agreement with the results of Argüello et al (2018) [63] who found Lactobacillus levels of about 60% in 5 week-old piglets. Lactobacilli might have been stimulated by the lactose present in the diet (4%), as these bacteria are able to use the simple milk sugar for their energy production [66].…”
Section: Effects Of Thymol and Tαg Supplementation On Gut Microbiotasupporting
confidence: 94%
“…Proteobacteria was the second most abundant phylum in our samples, after Firmicutes. This observation is largely in agreement with the literature, although the reported relative abundances of these phyla fluctuate with values roughly ranging between 60% and 95% for Firmicutes and between 2% and 30% for Proteobacteria [62][63][64][65]. A variety of factors might explain the discrepancy between studies, such as differences in diets, antimicrobial use, age of the animals, breed, and environment [34].…”
Section: Effects Of Thymol and Tαg Supplementation On Gut Microbiotasupporting
confidence: 88%
See 1 more Smart Citation
“…3A). It is also dominant in pigs (Argüello et al, 2018), and plays a protective role in cirrhotic human patients (Argüello et al, 2018). The abundance of Ruminococcaceae remarkably reduced in chronic heart failure human patients compared to the controls at the genus level (Luedde et al, 2017).…”
Section: Comparison Of Rectal Microbes Between the Ket And Con Groupsmentioning
confidence: 99%
“…A balanced gut microbial ecosystem serves as the crucial defense against colonization and infection with enteric pathogens [14,48,49]. Salmonella infection could have negatively impact on gut intestinal microbiome composition by diminishing the abundances of Firmicutes including Lactobacillus and Bifidobacterium, and simultaneously favoring the dominance of Proteobacteria inducing follow-up opportunistic infections [5052]. In our study, we observed the raised abundances of Salmonella and Enterobacter with overall reduced bacterial species diversity following ST challenge in mice, whereas LC + mcra pre-administration successfully prevented the negative shifting of gut microbiota composition induced by ST infection.…”
Section: Discussionmentioning
confidence: 99%